Oral administration of milk fermented with Lactobacillus delbrueckii ssp. bulgaricus OLL1073R-1 to DBA/1 mice inhibits secretion of proinflammatory cytokines - Kano, Hiroshi (Kluwer Academic Publishers, 2002)
We have previously shown that oral administration of skimmed milk(SM) fermented with Lactobacillus delbrueckii ssp. bulgaricus OLL1073R-1 (OLL1073R-1/SM) to DBA/1 mice inhibited the development of collagen-induced arthritis (CIA). In this study, our aim was to examine possible mechanisms of inhibiting the development of CIA. We studied the effect of OLL1073R-1/SM on cytokine secretion from cells of popliteal lymph nodes (lymph node cells; LNC) of mice. The results showed that feeding OLL1073R-1/SM inhibited secretion of proinflammatory cytokines such as interferon γ (IFN-γ), interleukin 6 (IL-6), tumor necrosis factor α (TNF-α) and the chemokine, monocyte chemoattractant protein 1 (MCP-1). The most prominent effect was inhibition of TNF-α. Secretion of IL-2 and IL-4 were not influenced. Feeding OLL1073R-1/SM inhibited secretion of proinflammatory cytokines produced by accessory cells, but not T cells. We conclude that CIA may be prevented via down regulation of secretion of proinflammatory cytokines such as IL-6, TNF-α and IFN-γ, and of the chemokine of MCP-1.